Sistem Informasi Jasa Pengurusan Dokumen Warga Negara Indonesia (Paspor) Berbasis Web - NDRURU, SAVERIA SELINGAN (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2024)
Computer-based information systems are information systems that use computers and other electronic machines to replace manual processes related to information communication for both internal and external purposes of the company. The distribution or delivery of information carried out on online information systems can be accessed by anyone and anywhere with the provision that they must have an internet connection. The purpose of this study is to study several theories and observations in the field in order to design a web-based passport service information system. The application development methodology used by the author is the UML method with a waterfall process model until the application creation stage. The programming used is Sublime Text using MySQL as its database. The expected result of the study is the creation of an application that can make it easier for the public to find information on passport services that can help in managing passports and documents that must be prepared. of course, with the creation of this application, it can also help companies in getting additional clients.